Identification Of The Most Common Problems During Lactation In Primipara Mothers - Saleha, Siti; Raudhati, Sri; Hilwa, Zaitun (Universitas Teuku Umar, 2025)
Breastfeeding problems that develop in the postpartum phase create conditions that negatively impact breastfeeding. Problems that often arise during lactation such as thoughts of insufficient milk, scarring of the nipples, blockage of milk flow, breast swelling, mastitis, breast abscesses, and flat nipples. The purpose of this study is to identify the most common problems during lactation in the first days after childbirth of primipara mothers. The research was conducted by crossectional studies on postpartum mothers by collecting data/variables on demographics and obstetrics as well as the manifestation of maternal problems during lactation. Data was collected by asking questions on a questionnaire sheet, then collected in excel, and conducted statistical analysis using the chi square test through the SPSS application. The results of this study are that the most common problem experienced by respondents is difficulty sleeping, out of 40 respondents there are 32 respondents (80%) who have difficulty sleeping day and night. The results of the statistical analysis stated that there was a significant relationship between parity and the respondents' sleep difficulties during lactation, problems with poor breastfeeding, problems of not being able to breastfeed their babies, problems of not being able to take care of their babies (P value=0.015; P value=0.032; P value= 0.012; P value = 0.029 in order) and there was no association between parity and the problem of loss of appetite during the lactation period (P value 0.071). The most common problem that occurs during lactation is trouble sleeping.